Peripheral blood markers predict prognosis and irAEs of stage IV driver gene-negative lung adenocarcinoma treated with ICIs - Li, Yu; Cao, Lei; Liu, Lei; Ding, Yawen; Cao, Feng (Frontiers in Immunology, 2025)
ObjectiveThis study aims to evaluate the prognostic significance of peripheral blood biomarkers in relation to outcomes and immune-related adverse events (irAEs) among patients with stage IV driver gene-negative lung adenocarcinoma receiving treatment with immune checkpoint inhibitors (ICIs).MethodsWe conducted a retrospective analysis of clinicopathological data from 102 patients diagnosed with stage IV driver gene-negative lung adenocarcinoma who were treated with ICIs at the Fourth Hospital of Hebei Medical University between January 1, 2019, and December 31, 2023. We employed the Kaplan-Meier method to perform a univariate analysis of progression-free survival (PFS) and overall survival (OS), generated survival curves, and assessed differences in survival between groups using the log-rank test. The Cox regression model was utilized for multivariate analysis of PFS and OS. Additionally, we assessed the predictive value of peripheral blood markers for irAEs using logistic regression models.ResultsThe 1-, 3-, and 5-year PFS rates for the cohort of 102 patients were recorded at 35.3%, 3.9%, and 0%, respectively; similarly, the OS rates at these time points were observed to be 66.7%, 8.8%, and 2.9%. Multivariate analysis identified that the prognostic nutritional index (PNI) and metastatic status served as independent prognostic factors influencing PFS outcomes in this patient population; furthermore, D-dimer levels, PNI, metastatic status, and the occurrence of irAEs emerged as independent prognostic indicators impacting OS rates among patients. Subsequent logistic regression analysis revealed that both platelet-to-lymphocyte ratio (PLR) and lymphocyte-to-monocyte ratio (LMR) functioned as independent predictors of irAEs with statistical significance (P=0.032; P=0.02).ConclusionFor patients with stage IV driver gene-negative lung adenocarcinoma undergoing ICI therapy, PNI and metastatic status can serve as initial predictors of PFS. Additionally, D-dimer levels, PNI, metastatic status, and the presence of irAEs can initially predict OS, aiding in the identification of populations that may benefit from ICI therapy in clinical practice. Furthermore, our findings indicate a need for heightened attention to PLR and LMR concerning the occurrence of irAEs.